Pengembangan Pariwisata Lokal lewat Pasar Jadoel: Strategi Wisata Alam Tirtosari - Rahmadani, Aulia Putri; Sulanam, Sulanam (Penerbit Goodwood, 2025)
Purpose: The purpose of this study is to analyze the impact of the Pasar Jadoel Establishment initiative, initiated by KKN Uinsa students on the development of local tourism in Penanggal Village, Lumajang. This study aims to examine how Pasar Jadoel can increase the attractiveness of Tirtosari Nature Tourism and attract more visitors, empower local small and medium enterprises (SMEs), identify and overcome challenges faced by Tirtosari Tourism in terms of management and marketing, and propose solutions to increase its potential. This study seeks to demonstrate the role of innovative tourism initiatives in revitalizing the local economy and promoting cultural heritage. Methodology/approach: The methodology used in the study is a descriptive qualitative approach with a case study design. This approach allows the researchers to analyze the development of local tourism through the establishment of Pasar Jadoel without influencing the subjects being studied. The research focuses on assessing the increase in visitor numbers at Wisata Alam Tirtosari as a result of the Pasar Jadoel initiative. Results/findings: The results of the study indicate that the initiative to establish Pasar Jadoel has had a positive impact on local tourism in Tirtosari Nature Tourism in several ways, one of which is the Increase in the Number of Visitors. There was a significant increase in the number of visitors to Tirtosari Nature Tourism after the establishment of Pasar Jadoel. Visitor data shows that Pasar Jadoel attracted more tourists during its operation. The market also provides a forum for local people to sell their products, which contributes to the economic empowerment of small and medium enterprises (MSMEs) in the area. This study shows that Pasar Jadoel serves as a viable strategy to increase local tourism and support community development in Penanggal Village, Lumajang. Limitations: This study has several limitations: The study only focuses on the short-term impacts of the Pasar Jadoel initiative, which may not fully capture the long-term impacts on local tourism and economic development. The study uses a descriptive qualitative study, the findings of which may be affected by researcher interpretation and bias, which may affect the objectivity of the results. Contribution: This study contributes to local tourism development through the initiative of establishing Pasar Jadoel. This study shows how the initiative can increase tourism appeal, empower the local economy, and promote cultural heritage. The findings can serve as a model for similar tourism development efforts in other areas, demonstrating the potential for local involvement in revitalizing tourism and supporting community development.